Early life factors on childhood overweight and obesity among preschoolers in Putrajaya, 2017 - Ahmad Fauzi, Fatimah (2017)
Background: Childhood obesity is becoming a global epidemic in this new era. According to WHO, the number of overweight children under the age of five in 2014 worldwide is estimated to be over 42 million and more than 70% of them are living in developing countries. Similar problem faced in Malaysia as being labelled as the fattest population in South East Asia.